"Boburname" and the Theater (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In article is speculated about contribution the Zahiriddin Babur in world civilization, his rich spiritual-cultural heritages, as well as, about scenic interpretation on scene uzbek theatre, recognized in all world as encyclopedic product "Baburname".